Antibacterial Activity of Graphene Oxide Nanosheet Against Salmonella Associated Food Contamination - Nawar Al-Janabi; Mohammed Al-Awady (Genius Publishing Group, 2021)
Salmonella is a Gram-negative bacterium and the causative agent of typhoid and salmonellosis. Fever, headache, nausea, vomiting, abdominal pain and diarrhea, are the common symptoms of salmonella infections. Graphene Oxide Nanosheet (GO Nanosheet) has been used as antimicrobial agents against many bacterial pathogens. However, the efficiency of GO Nanosheet to prevent Salmonella infections is poorly understood. Therefore, in this study, we used the chicken muscle attachments model to determine the antibacterial activity and binding capacity of GO Nanosheet against Salmonella typhi and Salmonella paratyphi. Results indicated that GO Nanosheet were significantly effective in blocking Salmonella attachment to chicken muscle. This study suggests an alternative strategy for reduction of Salmonella contamination in fresh and frozen food products
Keywords: Salmonella; Graphene Oxide Nanosheet; Food contamination